Insoluble-bound polyphenols of adlay seed ameliorate H2O2-induced oxidative stress in HepG2 cells via Nrf2 signalling. (30th September 2020) - Yao, Yijun; Wang, Hongling; Xu, Feiran; Zhang, Yiyi; Li, Zhifang; Ju, Xingrong; Wang, Lifeng
Highlights: Each fraction of insoluble-bound polyphenol extracts from adlay seed was obtained by separating with Sephadex LH-20 column and semi-preparative HPLC. Ferulic acid, the main active component of insoluble-bound polyphenol in adlay seed could increase the activity of GSH-PX, CAT, γ-GCS. And it could also ameliorate H2 O2 -induced oxidative stress in HepG2 cells via Nrf2 signalling. Abstract: In this study, protective effects of insoluble-bound polyphenol extracts from adlay seed against H2 O2 -induced oxidative stress in HepG2 cells were investigated. Each fraction of insoluble-bound polyphenol extracts from adlay seed was obtained by separating with Sephadex LH-20 column and semi-preparative HPLC. Ferulic acid was found being the main active component of insoluble-bound polyphenol in adlay seed. The cytoprotective effects of ferulic acid against oxidative challenge were determined by cell viability, intracellular reactive oxygen stress change in HepG2 cells, western blot and apoptosis by flow cytometry. Ferulic acid had a positive correlation with cell viability and a negative correlation with apoptosis. Ferulic acid treatment increased the activity of GSH-PX, CAT, γ-GCS. Moreover, the nuclear factor E2 related factor (Nrf2) protein expression in the ferulic acid group positively correlated with the HO-1, GCLC and NQO1 protein levels. Thus the results demonstrated that ferulic acid, the main active component of insoluble-bound polyphenol in adlay seed could ameliorate H2 O2 -induced oxidative stress in HepG2 cells via Nrf2 signalling. The research can provide a reference for the in-depth study of its regulatory mechanism and the development of antioxidant related functional food and health products.